Analisis pencemaran antropogenik dan struktur komunitas diatom planktonik sebagai indikator pencemaran perairan di Selat Air Hitam - Miduk Tampubolon; Yusni Ikhwan Siregar; Sofyan Husein Siregar (Jurnal Zona, 2017)
The present study aimed at identify population characters pollution source which affect water fertily nitrate, phospate, abundance as well as community structure of planctonic diatomae were measured. Nine sampling station of three location were established a long the Selat Air Hitam water. Appearently domestic activity, marine traffic, sago processing plant and community economic had affected on water fertility  due to effluent water that entered the water. Nitrate analysis showed a range of 187,5 to 262,5 µg/L mean while phospate consentration appear 28,8- 241,2 µg/L, silicate consentration appear 30,4-32,9 µg/L. Plactonic diatomae abundance came up 2400 to 3800 cell/L of nine genera. Biodiversity index of range  (1 kurang dari atau sama dengan H’ kurang dari atau sama dengan 3), while smiliarity index (0,5 kurang dari atau sama dengan E kurang dari atau sama dengan 1) and dominancy index (0,5 kurang dari atau sama dengan Ekurang dari atau sama dengan 1). Those index indicate nthe Selat Air Hitam waters in a medium pressure, however ecosystem condition is stable. Nitrate, phospate and silicate positively and significantly correlated with diatomae abundance ( p kurang dari 0,05). TSS level appeared 18,33 – 45,00 mg/l and BOD berkisar 3,73 – 5,07 mg/l. Regression analysis showed that nitrate and phospate had a mayor affect to diatomae abundance.